2019
DOI: 10.12659/msm.915503
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dexmedetomidine-Mediated Insulin-Like Growth Factor 2 (IGF2) Signal Pathway on Immune Function and Invasion and Migration of Cancer Cells in Rats with Ovarian Cancer

Abstract: Background The aim of this study was to explore the effect of dexmedetomidine (DEX)-mediated insulin-like growth factor 2 (IGF2) signal pathway on immune function and cancer cell invasion and migration in rats with ovarian cancer. Material/Methods Forty rats with ovarian cancer were divided into 4 groups: model group, and low dose (0.2 μg/kg/hour DEX), medium dose (1.0 μg/kg/hour DEX), and high dose (5.0 μg/kg/hour DEX) DEX groups. In addition, 10 Fischer344 rats were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Number of migrated cells were measured using an inverted microscope (Leica). Six elds were randomly selected, and the average was calculated [34].…”
Section: Transwell Assaysmentioning
confidence: 99%
“…Number of migrated cells were measured using an inverted microscope (Leica). Six elds were randomly selected, and the average was calculated [34].…”
Section: Transwell Assaysmentioning
confidence: 99%
“…Number of migrated cells were measured using an inverted microscope (Leica). Six fields were randomly selected, and the average was calculated [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…Besides, a previous study also suggested that DEX treatment could inhibit OC growth and the tumor weight of OS rats in vivo (Cai and Tang, 2017). Recently, Lei Hou et al found that DEX could improve the immune function of OC rats and inhibit the invasion and migration of OC cells via inactivating the insulin-like growth factor 2 signaling pathway (Tian and Hou, 2019). Meanwhile, in this present study, DEX also presented a dose-dependent promoting role in OC cell apoptosis, with increased expression of cleaved caspase 3 and Bax while declined expression of Bcl-2 shown after DEX treatment.…”
Section: Discussionmentioning
confidence: 97%